Badminton: Steps to success - Grice, T. (Human Kinetics, 2008)
Players clocking shuttlecocks at speeds of 200 miles per hour, new scoring rules, and nonstop action make badminton one of the fastest racket sports in the world. With Badminton: Steps to Success you will learn the skills and tactics to excel at the highest level. Through detailed, fully illustrated instruction, you will develop precision, power, and finesse as you use this step-by-step guide to master serves, forehands, backhands, clears, drop shots, smashes, drives, and more. Badminton: Steps to Success also breaks down common errors players make and provides corrective techniques to pinpoint problems and improve execution. Over 100 drills will further enforce correct technique, with designated drills for tactical practice, conditioning, and teamwork for doubles play. Badminton: Steps to Success - part of the popular Steps to Success Sports Series with more than 1.5 million copies sold - is your ticket to winning play.